Sentinel-3 Altimetry Thematic Products for Hydrology, Sea Ice and Land Ice - Jérémie Aublanc; Julien Renou; Fanny Piras; Karina Nielsen; Stine K. Rose; Sebastian B. Simonsen; Sara Fleury; Stefan Hendricks; Nicolas Taburet; Giovanni D’Apice; Anouk Chamayou; Pierre Féménias; et al. (Scientific Data)
Abstract This paper presents the Copernicus Sentinel-3 level-2 altimetry Hydro-Cryo “Thematic Products”, operationally generated by ESA since September 2023. In comparison to previous product versions, the level-2 processing is now performed through three independent chains, generating three families of “Thematic Products”, for measurements acquired over hydrological, sea ice and land ice areas, respectively. Prior to the operational deployment, a full mission reprocessing was achieved with the thematic processors, providing a complete and harmonised dataset to the users. In this paper, the new architecture of the ground segment processing is presented, along with the major algorithmic developments. The main data content of the Thematic Products is also described, to indicate the key product variables for the end users. The Thematic Products have been evaluated by the Sentinel-3 Mission Performance Cluster (MPC) experts. The major results and outcomes are presented, showing the significant performance improvement achieved in comparison to previous processing versions.